Use of Insoluble Dietary Fiber and Probiotics for Bowel Preparation Before Colonoscopy: A Prospective Study. Issue 2 (24th April 2022) - Kudou, Kensuke; Kimura, Koich; Tsutsumi, Ryosuke; Hashimoto, Naotaka; Wada, Hiroya; Ikeda, Tetsuo
Abstract : Background: In screening colonoscopy, patients usually have to ingest large amounts of bowel-cleansing agents, including polyethylene glycol (PEG). This is difficult and has various side effects; thus, patients avoid undergoing a colonoscopy. We tested a novel bowel preparation method before colonoscopy using insoluble dietary fiber and probiotics (PB). Methods: This was a prospective clinical study conducted between October 2018 and March 2019 at a general hospital. Forty participants were randomly assigned to low-volume PEG solution diet (MoviPrep), wheat bran fiber (WBF) and probiotic Bifidobacterium animalis subsp. lactis GCL2505 (PB GCL2505), or standard-volume regimen (1.0 to 1.5 L of MoviPrep) (control group). The patient compliance and the quality of bowel preparation were evaluated. Results: Forty individuals aged 38 to 83 years were randomly assigned to the WBF with PB (n=20) and control (n=20) groups. All participants underwent bowel preparation before colonoscopy according to each protocol. The mean required volume of MoviPrep was significantly lower in the WBF with PB group than in the control group (582.5 vs. 1305 mL, P <0.0001). Successful bowel-cleansing rates were not significantly different between the 2 groups; however, the ratio of the Harefield Cleansing Scale grades C and D was significantly lower in the WBF with PB group than in the control group ( P =0.0471). Conclusions: The intake of WBF and GCL2505 before colonoscopy reduces the required PEG quantities while maintaining bowel-cleansing quality. This novel, minimally invasive pretreatment method makes colonoscopy more accessible contributing to the prevention and early treatment of colorectal cancer.